Removal of Procion Red MX-5B and Remazol Brilliant Violet 5R from aqueous solution by adsorption using selected agricultural wastes - Fatin Izzaidah Anuar, 1991-, author; Tony Hadibarata, supervisor; Fakulti Kejuruteraan Awam (2015)
Project Paper (Sarjana Muda (Kejuruteraan Awam - Alam Sekitar)) - Universiti Teknologi Malaysia, 2015